An Analysis of The Role of Law In The Formation of Social Identity In Urban Communities - Fabio M, Sura; Huseini, Martani (Pelopor Publikasi Akademika, 2024)
Regionally-Owned Enterprises (BUMD) have the goal of managing strategic sectors for the regions, supervising, and ensuring the benefits of resource management in order to achieve optimal community welfare. PT. PITS is engaged in the provision of drinking water, but in reality it has not yet achieved its goals. The post-positivist approach is used so that this research can combine theory with phenomena found in the field. The results of this study show that there are problems in the dimensions of shared values, styles, and skills. These problems are expected to be solved by using a collaborative governance approach. PT. PITS must be problem-driven first, when the problem has been solved, PT. PITS must also be opportunity-driven. With the involvement of non-state actors , it is hoped that it can help the performance of PT. PITS in achieving its goals.